Secondary Metabolites and Antioxidant Activity of Methanol Extract of Castanopsis costata Leaves - Alkandahri, Maulana Y.; Nisrihadi, Leo; Salim, Emil (Pharmacology and Clinical Pharmacy Research)
Castanopsis costata (C.costata) leaves were empirically used by people in North Sumatera, Indonesia, as an antioxidant dietary supplement. However, its pharmacological effect has not been scientifically explored. The purpose of this study was to identify the secondary metabolites and antioxidant activity of C. costata. The leaves were cold extracted with methanol. The secondary metabolites were determined using thin layer chromatography. Its antioxidant activity was investigated using 1,1-diphenyl-2-picrylhydrazyl (DPPH) method. The results showed that methanol extract of C. costata leaves consisted of alkaloids, flavonoids, glycosides, anthraquinone glycosides, tannins and triterpenoids. The methanol extract of C. costata leaves showed comparable antioxidant activity with vitamin C, IC50 35.56 Î¼g/ml and 14.17 Î¼g/ml, respectively.Keywords: Castanopsis costata leaves, methanol extract, antioxidant, DPPH, vitamin C.